2006
DOI: 10.1143/jjap.45.l111
|View full text |Cite
|
Sign up to set email alerts
|

Surface Control Process of AlGaN for Suppression of Gate Leakage Currents in AlGaN/GaN Heterostructure Field Effect Transistors

Abstract: We proposed a surface control process for suppressing the tunneling leakage of Schottky gates on AlGaN/GaN heterostructures. For the recovery of nitrogen-vacancy-related defects and reduction in the amount of oxygen impurities at the AlGaN surface, the process consisted of nitrogen radical treatment, the deposition of an ultrathin Al layer, UHV annealing and finally the removal of the Al layer. Ni/Au Schottky gates fabricated on processed AlGaN surfaces showed pronounced reduction in leakage current and a clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…This process produces a thin Al 2 O 3 layer and improves electronic and chemical properties of the AlGaN surface by reducing the amount of defects related to nitrogen vacancies and oxygen. 55 After this, the SiN x film was deposited by the electron cyclotron resonance chemical vapor deposition ͑ECR CVD͒ technique ͑the sample was at 260°C, the power was 100 W, and the deposition rate was about 10 nm/min͒ using SiH 4 and N 2 with a flow rate of 10 SCCM ͑SCCM denotes cubic centimeter per minute at STP͒, proceeded by 1 min of ECR CVD N 2 plasma treatment in the same chamber ͑the power was 50 W and the flow rate was 10 SCCM͒. We checked the thickness of the SiN x layer by ellipsometric measurements of Si control samples mounted close to the AlGaN/GaN one and confirmed that it was approximately equal to 20 nm.…”
Section: A Device Fabricationmentioning
confidence: 99%
“…This process produces a thin Al 2 O 3 layer and improves electronic and chemical properties of the AlGaN surface by reducing the amount of defects related to nitrogen vacancies and oxygen. 55 After this, the SiN x film was deposited by the electron cyclotron resonance chemical vapor deposition ͑ECR CVD͒ technique ͑the sample was at 260°C, the power was 100 W, and the deposition rate was about 10 nm/min͒ using SiH 4 and N 2 with a flow rate of 10 SCCM ͑SCCM denotes cubic centimeter per minute at STP͒, proceeded by 1 min of ECR CVD N 2 plasma treatment in the same chamber ͑the power was 50 W and the flow rate was 10 SCCM͒. We checked the thickness of the SiN x layer by ellipsometric measurements of Si control samples mounted close to the AlGaN/GaN one and confirmed that it was approximately equal to 20 nm.…”
Section: A Device Fabricationmentioning
confidence: 99%
“…Extremely weak temperature dependence was observed in I v , which is the same behavior as the leakage current in large area AlGaN / GaN Schottky diodes. 7 We investigated the leakage current transport of large area Schottky diodes with a diameter of 200 m -600 m and proposed a model based on surface donor. 8,9 Here, the width of the Schottky barrier was assumed to be reduced due to the presence of unintentionally introduced surface donors, such as nitrogen vacancy defects or oxygen impurities.…”
Section: -3mentioning
confidence: 99%
“…3(b)), some of the As 2 O 5 was converted to As 2 O 3 by the strong deoxidization effect of aluminum. 34 The self-cleaning effect is usually explained in terms of the chemical reaction between the native oxide and TMA. Recent computational results 35 on the thermodynamic Gibbs free energy indicate that Al 2 O 3 can be formed by As 2 O 3 and TMA producing reaction products such as As 4 , As(CH 3 ) 3 , C-H groups, H 2 O, and CO 2 .…”
mentioning
confidence: 99%